Find two rational expressions that have a sum of 9-9x/x^2-9
I need steps not just answers
Math Analysis - Ryan, Sunday, October 12, 2008 at 4:23pm
First, I assume you mean (9-9x)/(x^2-9)?
Math Analysis - Damon, Sunday, October 12, 2008 at 4:47pm
Making the same assumption as Ryan
a(x+3) + b(x-3) = 1-x
solve and get a =-1/3, b=-2/3
9 [(-1/3)/(x-3) -(2/3)/(x+3)]
= -3/(x-3) -6/(x+3)
Math Analysis - Ryan, Sunday, October 12, 2008 at 4:53pm
If my assumption is true, you could simply use 9/(x^2-9) + -9x/(x^2+9), as these are both rational expressions, I think.